1983
DOI: 10.1007/bf01906467
|View full text |Cite
|
Sign up to set email alerts
|

The influence of arterial pressure changes on blood volume replacement after acute hemorrhage in the alert rat

Abstract: The fluid content of circulating blood was followed continuously by conductometric measurement of large vein hematocrit in the alert rat. Arterial pressure was registered simultaneously. 2.5-23% of the determined blood volume was withdrawn rapidly and the changes of fluid content (delta v) calculated. Determinations of plasma protein showed that calculated delta v(delta vapp) may exceed true delta v due to transvascular fluid inflow by maximally 38%. A very fast phase of fluid inflow into the circulation (delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As mentioned, the method was developed in order to substantiate the results of experiments in which very rapid transvascular fluid movements were demonstrated essentially by blood conductometry (3,4,5). For the most part this has successfully been done qualitatively in the present experiments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As mentioned, the method was developed in order to substantiate the results of experiments in which very rapid transvascular fluid movements were demonstrated essentially by blood conductometry (3,4,5). For the most part this has successfully been done qualitatively in the present experiments.…”
Section: Discussionmentioning
confidence: 93%
“…In previous papers (3,4,5), conductometrically measured hematocrit (hct) was monitored as an indicator of fluid content of blood flowing in various parts of the circulatory system of the rat. The assumption of a correlation between hct changes and transvascular fluid movements was substantiated by occasional determination of both hct and total plasma protein in situations where sufficiently large and sustained changes took place for reliable measurements.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous papers (1,2), in which it was shown that very rapid changes of protein concentration accompany hematoerit changes in acute hemorrhage, changes of plasma volume were followed by continuous registration of large vein hematocrit by means of conductometry while producing in the present experiments pulsatile changes of blood volume of various fixed amplitudes and period lengths, thus varying blood withdrawal rates within wide limits. Beside hct, arterial pressure and heart rate were determined for assessment of their influences on fluid exchange between the two compartments of extracellular space.…”
Section: Introductionmentioning
confidence: 80%
“…The conductivity cell was calibrated during these and previous experiments to deliver hematocrit values by repeated determinations of packed cell volume in 30-40 ~tl samples of blood passing the cell during the experiment. Details of all procedures have been reported (1,2).…”
Section: Femalementioning
confidence: 99%
See 1 more Smart Citation